ALTERNATIVE CLOSURE-FASTENERS FOR ELDERLY-FRIENDLY ADAPTIVE CLOTHING: A CASE STUDY OF ELDERLY WOMEN - Ghasany, Fatimah; Feny Puspitasari (Universitas Negeri Yogyakarta, 2025)
The growth of the elderly population in Indonesia is predicted to increase in 2025. Changes in the ratio of potential support for the elderly are decreasing, thereby affecting the fulfillment of the elderly's needs. The elderly have difficulty dressing independently due to their declining physical condition. The need for adaptive clothing answers the solution but is rarely found in Indonesia. Previous studies have only focused on physical disabilities, cerebral palsy, and arthritis. This study focuses on problematic factors in dressing for the elderly and the concept of adaptive clothing design that is friendly to the elderly regarding the closure-fastener access feature. This study uses the design thinking method. The respondent selection technique uses the purposive sampling method with criteria 1) women aged at least 60 years, 2) communicating well, 3) having difficulty dressing, and 4) having complaints of physical conditions. Data collection techniques use trials and interviews. Alternative closure features that are tested are magnet, velcro, and zipper. The test results show that the velcro closure feature has a high percentage of access to use in terms of comfort and safety, the magnetic closure feature has a high rate in comfort aspect equivalent to velcro, and the zipper closure feature has a low percentage in all aspects tested. Based on the trial results, the blouse model with velcro closure is most recommended. Furthermore, this research can be expanded to explore adaptive clothing further due to the limited availability of adaptive clothing in Indonesia.